Alone together why we expect more from technology and less from each other - Turkle, Sherry (Tantor, 2014)
MIT professor Sherry Turkle tackles the precarious balance between isolation and connectivity introduced by the growth of social networking technologies.
Hard copy version record
Keywords: Information technology -- Social aspects; Interpersonal relations; Human-computer interaction; Technologie de l'information; Aspect social; COMPUTERS; General; Information technology; Social aspects; Downloadable audio books; Audiobooks; Livres audio